An overview of the osseous palmar sesamoid in Anura, with the particular case of some Rhinella species - Manzano, Adriana Silvina (2023)
Background. Sesamoids are generally regarded as structures that are not part of the tetrapod body plan. The presence of a palmar sesamoid is assumed to serve as a distribution point for the forces of the flexor digitorum communis muscle to the flexor tendons of the digits, which are embedded in the flexor plate. It has been considered that the palmar sesamoid is present in most anuran groups, and it has been suggested that it acts by inhibiting the closing of the palm, preventing grasping. Typical arboreal anuran groups lack a palmar sesamoid and flexor plate, a pattern shared with other tetrapod groups, which can retain a reduced sesamoid and flexor plate. We focus on the anatomical structure of the Rhinella group, which includes species that present an osseous palmar sesamoid and climb bushes or trees to avoid depredation or escape dangerous situations, and can exhibit scansorial and arboreal behaviors. We also add data on the bony sesamoids of 170 anuran species to study the anatomy and evolution of the osseous palmar sesamoid within this amphibian group. Our objective is to bring an overview of the osseous palmar sesamoid in anurans, unveiling the relationship between this element of the manus, its phylogeny, and the anuran habitat use. Methods. Skeletal whole-mount specimens of Rhinella were cleared and double-dyed to describe the sesamoid anatomy and related tissues. We review and describe the palmar sesamoid of 170 anuran species from CT images downloaded from Morphosource.org, representing almost all Anuran families. We performed an standard ancestral state reconstruction by optimizing two selected characters (osseous palmar sesamoid presence, distal carpal palmar surface) along with the habitat use of the sampled taxa, using parsimony with Mesquite 3.7. Results. Our primary finding is that sesamoid optimization in the anuran phylogeny revealed that its presence is associated with certain clades and not as widespread as previously anticipated. Additionally, we will also be delving into other important outcomes of our study that are relevant to those working in the field of anuran sesamoids. The osseous palmar sesamoid is present in the clade Bufonidae-Dendrobatidae-Leptodactylidae-Brachicephalidae that we named as PS clade, and also in the archeobatrachian pelobatoid Leptobranchium, all strongly terrestrial and burrowing species, though with exceptions. The osseous palmar sesamoid is always present in Bufonidae, but varies in form and size, depending on the mode that they use their manus, such as in the Rhinella margaritifera which has a cylindrical one and also grasping abilities that involve closing the manus. The scattered presence of the bony palmar sesamoid among anuran clades raises the question whether this sesamoid can be present with a different tissular composition in other groups.